Sacrificial rite of the komi-permyaks n the village of Bolshaya Kocha - Goleva, T. G. (Perm Federal Research Centre Journal, 2020)
The history of the sacrificial tradition of a Komi-Permian village is studied in the article. This tradition is known as «bykoboy» («slaughter of a bull») and is dedicated to the day of St Florus and Laurus. The tradition was distinguished by the amount of the sacrifice offered. The author clarifies that the holiday complex, in addition to the ritual of sacrifice and a common meal, included a prayer service, consecration of horses, races and a fair. The order and some conditions of the rituals would change from year to year. In particular, some changes were related to restrictions imposed by local authorities. Researchers’ interest in the unusual tradition has led to its renown in wider circles. As a result, at the beginning of the XX century, church and community representatives began to pay special attention to the rite. In order to eradicate the sacrificial rituals, the clergy undertook a number of measures to enlighten the people. It is commonly believed that before the First World War the rite was banned. Subsequent historical events in the country contributed to the extinction of the tradition. At the turn of the XX-XXI centuries local residents revived the sacrificial ritual. The holiday ceremonial complex in the restored version slightly differs from the original tradition and has different symbolic meaning. The spread of information about the rite in our time has caused the emergence of negative statements, which led to the rejection of its public performance in 2018. Both in the past and in the XXI century, the rite of sacrifice performed the function of uniting the people, having conditioned the conduct of educational activities.